1999
DOI: 10.1210/mend.13.5.0272
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Insl3 Gene Causes Bilateral Cryptorchidism

Abstract: The sexual dimorphic position of the gonads in mammals is dependent on differential development of two ligaments, the cranial suspensory ligament (CSL) and the gubernaculum. During male embryogenesis, outgrowth of the gubernaculum and regression of the CSL result in transabdominal descent of the testes, whereas in the female, development of the CSL in conjunction with failure of the gubernaculum development holds the ovaries in a position lateral to the kidneys. Several lines of evidence suggest that regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
226
0
15

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 529 publications
(247 citation statements)
references
References 30 publications
6
226
0
15
Order By: Relevance
“…This was originally reported using the mouse brain receptor (25,26) but is now also observed for the human relaxin receptors LGR7 and LGR8. 3 For relaxin-LGR7 binding we showed that the large contribution of the arginines to the binding energy is due to their chelation by two carboxyl groups (24). These relaxin binding residues as identified on LGR7 are also present on LGR8 but do not seem to play the important role in the cross-reactivity.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This was originally reported using the mouse brain receptor (25,26) but is now also observed for the human relaxin receptors LGR7 and LGR8. 3 For relaxin-LGR7 binding we showed that the large contribution of the arginines to the binding energy is due to their chelation by two carboxyl groups (24). These relaxin binding residues as identified on LGR7 are also present on LGR8 but do not seem to play the important role in the cross-reactivity.…”
Section: Resultsmentioning
confidence: 86%
“…This work signaled a new approach to a long-standing problem of cryptorchidism in humans (3,4) where the problem of testicular retention is exacerbated by a predisposition for testicular cancer (5,6). The availability of synthetic RLF and RLF derivatives (7)(8)(9)(10)(11)(12) has provided the opportunity to investigate several aspects of the role of RLF in gonadal migration.…”
mentioning
confidence: 99%
“…In parallel, the inverse experiment was conducted by increasing the dose of the inhibitor Ades- (1)(2)(3)(4)(5)(6)(7)(8) in the presence of a uniform concentration (2 ng/ml) of hRLF. The two dose-response curves crossed at a concentration of 1.5 ng/ml, indicating that Ades-(1-8) behaves as a competitive antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…Cryptorchid mice with normal gonadotropin and intratesticular T levels show complete absence of postmeiotic germ cells (23). Why the cryptorchid LuRKO testes showed more advanced spermatogenesis is an intriguing question.…”
Section: Discussionmentioning
confidence: 99%